1990
DOI: 10.1039/c39900001107
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity studies of aldolase enzymes for use in organic synthesis

Abstract: The preparation of (3-hydroxy-a-amino acids from glycine and various aldehydes by-aldolase enzymes is examined; attention is focused on substrate structural requirements, with stereoselectivity of the aldol reactions also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The synthesis of 5 required an appropriately substituted l - erythro - anti -β-hydroxy-α-amino acid, which is the only requirement for the preparation of carbacephalosporin 3 in optically active form if the β-lactam is prepared by N −C 4 bond closure . In previous studies, our laboratory has shown that an enzymatic approach could be used to synthesize these amino acids . The stereochemistry of the carbacephalosporin is determined by choosing the appropriate β-hydroxy-α-amino acid (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of 5 required an appropriately substituted l - erythro - anti -β-hydroxy-α-amino acid, which is the only requirement for the preparation of carbacephalosporin 3 in optically active form if the β-lactam is prepared by N −C 4 bond closure . In previous studies, our laboratory has shown that an enzymatic approach could be used to synthesize these amino acids . The stereochemistry of the carbacephalosporin is determined by choosing the appropriate β-hydroxy-α-amino acid (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The diastereomeric purity of chrysobactin (1) was confirmed by analysis of its o-phthalaldehyde (OPA) derivatives using reversed-phase (C-18) HPLC with fluorescence detection (Lotz et al 1990). A 2% sodium dodecyl sulfate (SDS) solution was prepared by dissolving 0.20 g of sodium dodecyl sulfate in 10 ml of 0.4 M sodium borate buffer (pH 9.5).…”
Section: Synthesis Of Chrysobactinmentioning
confidence: 99%
“…Current variation of substituents at the C-4 position of monobactams most often requires access to the corresponding β-hydroxy amino acid precursors 7 . While some naturally-occuring β-hydroxy amino acids, such as serine ( 7 , R = H) and threonine ( 7 , R = Me), are readily available, others are much less common or require total syntheses themselves . Alternatively, optically pure β-hydroxy acids 10 are readily available by asymmetric enzymatic and chemical reductions.…”
mentioning
confidence: 99%